How does D&O insurance affect corporate environmental investment? - Liu, Jiamin; Jiang, Yalin; Gan, Shengdao (Frontiers in Environmental Science, 2022)
Directors’ and officers’ liability insurance (D&O insurance), an important tool for diversifying and transferring risks of managers, plays a crucial role in corporate investment decisions, including corporate environmental investment decisions. However, the relationship between D&O insurance and corporate environmental investment remains unknown. Using a sample of Chinese listed firms, this study examines whether and how D&O insurance affects corporate environmental investment from 2008 to 2019. We find that D&O insurance is negatively associated with corporate environmental investment. This result is consistent with the results of a series of robustness tests. Further analyses show that D&O insurance impedes corporate environmental investment by driving executives to seek private benefits, especially monetary benefits. Moreover, the negative effect of D&O insurance on corporate environmental investment is more pronounced in low-polluting and highly competitive industries. However, this negative relationship is mitigated by political connections. The findings contribute to the literature by providing empirical evidence on the involvement of D&O insurance in influencing corporate environmental investment decisions.